2007
DOI: 10.1007/s00383-007-1964-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of congenital tracheoesophageal fistula with esophageal atresia on the basis of gap length

Abstract: Congenital tracheoesophageal fistula (TEF) with esophageal atresia (EA) is not an uncommon disease of newborns. Several classifications have been advocated for predicting the outcomes of these patients but all are physiological and concentrated on associated medical condition that influences survival. We emphasize a new classification on the basis of gap between two esophageal pouches to define the magnitude of surgical problems in the primary repair and correlate them with the outcomes in terms of anastomotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 22 publications
1
49
1
2
Order By: Relevance
“…3,6,7 Approximately 25% of infants with esophageal atresia will develop postanastomotic fibrotic strictures, and the incidence of such strictures has been shown to increase with increasing esophageal gap length. 22,23 At the University of Minnesota, we serve as a referral base for the management of long-gap esophageal atresia and patients previously treated for strictures or fistula leaks. Our technique, developed during a decade of experience, is to dilate early and vigorously after primary repair to cause the stricturing tendency to relent and prevent dense scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,7 Approximately 25% of infants with esophageal atresia will develop postanastomotic fibrotic strictures, and the incidence of such strictures has been shown to increase with increasing esophageal gap length. 22,23 At the University of Minnesota, we serve as a referral base for the management of long-gap esophageal atresia and patients previously treated for strictures or fistula leaks. Our technique, developed during a decade of experience, is to dilate early and vigorously after primary repair to cause the stricturing tendency to relent and prevent dense scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of our patients had anastomotic leak in postoperative period. Studies have shown that apart from associated comorbidities and congenital anomalies, the complications and mortality is an outcome of gap length [14,15]. The long gap is associated with high The mortality in the Group B was 60%.…”
Section: Discussionmentioning
confidence: 99%
“…The suture material, type of anastomosis, anastomotic tension, ischemia, anastomotic leak and the presence of GER are the main factors affecting the development of anastomotic strictures [4]- [7]. The technique intraoperation and the way of anastomosis are very important for post-operative complications preventing.…”
Section: Discussionmentioning
confidence: 99%